GROSS ANATOMY OF MALE REPRODUCTIVE SYSTEM AND HISTOLOGY OF TESTIS AND VAS DEFERENS IN FRESHWATER CRAB BARYTELPHUSA CUNICULARIS (WESTWOOD 1836) (DEACAPODA: CRUSTACEA) - U. D. SHERKHANE,; M. U. PATIL,; G. S. PANDE, (The Bioscan, 2010)
This study provides the description of the gross anatomy and histology of the male reproductive system of B. cunicularis. Results of present probe showed that the male reproductive system consists of a pair of testes, a pair of vas deferens ending into ejaculatory ducts and a pair of penises. Two pairs of gonopods (modified pleopods) are also present which are known to serve as copulatory organs which transfer the spermatophores into female gonopores. The macroscopic anatomy of the testes showed a similar pattern to that described in other brachyuran species: the paired testes, H like appearance, presence of gonopods, etc. Histologically, the testes consist of large number of testicular lobes containing spermatogonial cells that differentiate into spermatocytes and a collecting duct. Each testis as a whole is covered by a connective tissue sheath, the tunica. Vas deferens is almost circular in cross section and has a fibrous sheath of connective tissue and muscle fibres. Is lined internally by a layer of glandular epithelium and its lumen contain large number of spermatophores that are being transported towards the penises.